"Virtus" e "appetitus animae": Note sul concetto di povertà in Bonaventura da Bagnoregio - Cuttini, Elisa (Miscellanea francescana, 2017)
The priority of the spiritual man over the carnal man in Bonaventure's anthropology is the foundation of the concept of poverty as an ethical virtue, in which the correct means are not calculated in relation to the impulses of senses but to the appetitus animae and coincides with limiting the use of material assets to the extent that they are strictly necessary for life. Embracing poverty means choosing freedom from earthly constraints in order to meet the needs of the interior life. Poverty, in fact, is not only intended as detachment from material goods, but is primarily an interior disposition to renounce the voluntas habendi. With regard to the attachment to temporal things, what is detrimental is not so much possessing them as desiring them. Therefore, in the words of Bonaventure, it can be affi rmed that "neither having nor loving riches is a useful, secure and joyful thing and also an act of perfect virtue." In this sense, with an apparently irrational expression, Bonaventure maintains that the fact of being poor is not an evil, but rather the unwillingness to be so. Poverty, freely chosen, far from debasing man, offers a privileged condition that allows him, freed from the desire for earthly goods, to easily accomplish the path of ascension to God described in the Itinerarium mentis in Deum, thus achieving the goal of true spiritual wealth and the complete satisfaction of every desire, which only reunion with the fi rst Principle can offer.